(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The following paper aims to analyse the impact of watching violent media on Children with Special Needs. It inculcates a Case Study of a Down Syndrome boy who got access to a number of violent films and videos through online and offline media. It is followed by an analysis of behavioural changes that are observed with the help of a professional Special Educator. The paper also includes a personal interview of the aforementioned expert in the field. A detailed analysis is followed by the ramifications and risks possible because of the impacts. The paper concludes with a detailed and well researched compilation as well as testing of improvement techniques.